Unintended Upper Uterine Wall Extensions at the Time of Cesarean Delivery: Risk Factors and Associated Adverse Maternal and Neonatal Outcomes - Peled, Tzuria; Saar, Noa; Muraca, Giulia M.; Sela, Hen Y.; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav (American Journal of Perinatology, 2024)
This study aims to estimate the frequency of unintended upper uterine wall extensions during cesarean delivery (CD) and identify associated risk factors and adverse outcomes.A multicenter retrospective cohort study was conducted, including patients who underwent CD between 2005 and 2021. Demographic factors, obstetric history, CD indications, delivery and surgical characteristics, adverse maternal and neonatal outcomes were compared between those with unintended upper uterine wall extensions during CD and those without extensions. Crude and adjusted estimates (odds ratios [ORs] and 95% confidence intervals [CIs]) were used.Among 30,517 patients meeting inclusion criteria, 117 (0.4%) had an unintended upper uterine wall extension. In univariate analysis, upper uterine wall extensions were associated with higher rates of intrapartum CD, second-stage CD, unplanned or emergency CD, CD following failed vacuum delivery or trial of labor after CD, chorioamnionitis, prolonged labor, increased vaginal exams, lower fetal head station, and higher birth weight. During surgery, higher rates of general anesthesia, significant intraperitoneal adhesion, fetal malpresentation, and fetal extraction by the leg were observed. Multivariable analysis identified fetal extraction not by head (adjusted OR [aOR]: 9.17, 95% CI: 5.35–15.73), vertex fetal presentation (aOR: 3.65, 95% CI: 1.81–7.35), second-stage CD (aOR: 3.07, 95% CI: 1.24–7.59), and trial of labor after cesarean (aOR: 2.04, 95% CI: 1.08–3.84) as significant risk factors for unintended upper uterine wall extensions. Additionally, upper uterine wall extensions were associated with higher rates of maternal and neonatal complications, including longer operating times, excessive bleeding, postpartum hemorrhage, intraperitoneal drainage, blood product transfusion, puerperal fever, paralytic ileus, Apgar score < 7 at 1 and 5 minutes, and fetal intracranial hemorrhage.Our study identifies risk factors for unintended upper uterine wall extensions during CD. While these extensions are infrequent, their occurrence is associated with increased maternal and neonatal morbidity.
Keywords: cesarean delivery; uterine incision extension; risk factors; T and J uterine extensions; adverse outcomes; fetal extraction; maternal complications; neonatal morbidity